Magnetophoretic transistors in a tri-axial magnetic field. Issue 21 (3rd October 2016) - Abedini-Nassab, Roozbeh; Joh, Daniel Y.; Albarghouthi, Faris; Chilkoti, Ashutosh; Murdoch, David M.; Yellen, Benjamin B.
Abstract : Magnetophoretic transistors switch magnetic particles and magnetically labeled cells between different paths in microfluidic channels in a tri-axial magnetic field. Abstract : The ability to direct and sort individual biological and non-biological particles into spatially addressable locations is fundamentally important to the emerging field of single cell biology. Towards this goal, we demonstrate a new class of magnetophoretic transistors, which can switch single magnetically labeled cells and magnetic beads between different paths in a microfluidic chamber. Compared with prior work on magnetophoretic transistors driven by a two-dimensional in-plane rotating field, the addition of a vertical magnetic field bias provides significant advantages in preventing the formation of particle clumps and in better replicating the operating principles of circuits in general. However, the three-dimensional driving field requires a complete redesign of the magnetic track geometry and switching electrodes. We have solved this problem by developing several types of transistor geometries which can switch particles between two different tracks by either presenting a local energy barrier or by repelling magnetic objects away from a given track, hereby denoted as "barrier" and "repulsion" transistors, respectively. For both types of transistors, we observe complete switching of magnetic objects with currents of ∼40 mA, which is consistent over a range of particle sizes (8–15 μm). The switching efficiency was also tested at various magnetic field strengths (50–90 Oe) and driving frequencies (0.1–0.6 Hz); however, we again found that the device performance only weakly depended on these parameters. These findings support the use of these novel transistor geometries to form circuit architectures in which cells can be placed in defined locations and retrieved on demand.